The role of Flexibility-Building Techniques in The development of Administrative processes and Performance Management from The perspective of the administrative staff at Tabuk University - Al-Fawaz, Najwa Mufawez Mofeez (Journal of Economic, Administrative and Legal Sciences, 2024)
The study aimed to explore the role of flexibility-building techniques in the development of administrative processes and performance management from the perspective of the administrative staff at Tabuk University. To achieve the study objectives, a descriptive approach was used, and a questionnaire was adopted as the data collection tool also, the study population consisted of the administrative staff at Tabuk University, with a sample of (50) participants was selected using systematic random sampling from the study population, the study results revealed that: 1) the mean scores were relatively high, with an overall mean score of (3.87) and a standard deviation of (0.78). 2) Moreover, among the sub-dimensions, the dimension number (1) (flexibility-building techniques) ranked first with a high mean score of (3.91) and a standard deviation of (0.88), 3) while the dimension number (2) (administrative processes) ranked last with a high mean score of (3.81) and a standard deviation of (0.87). 4)Furthermore, the study indicated that there were no statistically significant differences in the domain of the role of flexibility-building techniques in the development of administrative processes and performance management from the perspective of the administrative staff at Tabuk University, attributed to the variables of (gender, academic qualification, and years of experience), as all domains obtained significance levels higher than (0.05). Based on these findings, the study highlighted the necessity of utilizing resilience-building techniques within universities by the Administrative staff to facilitate administrative processes, alleviating administrative work pressures, and saving time. The study also recommended conducting training courses that contribute to training university administrative staff on how to apply resilience-building techniques.
Keywords: flexibility-building techniques; administrative processes; performance management